An epidemiological perspective of the pathology and etiology of sarcoidosis - Sawahata, Michiru; Sugiyama, Yukihiko (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
To update current knowledge on the pathology and etiology of sarcoidosis, here we review previous epidemiological research and discuss age-related differences and historical changes in the clinical characteristics of sarcoidosis we identified over the last four decades in Japan. Extrathoracic lymph node involvement was more common in young patients, while extrathoracic involvement of non-lymphatic organs and hypercalcemia were more common in older patients. Most patients in their 20s presented with bilateral hilar lymphadenopathy, but this was consistently less common among older patients. Over time, the distribution of age at diagnosis has shifted toward the older age group in the United States, Denmark, and Japan. In Japan, the incidence rate has been decreasing among young people, but there has consistently been a second peak among postmenopausal women. Age-related differences in the clinical presentation of sarcoidosis may reflect the pathways of causative antigens and the strengthening of immunoregulatory mechanisms with age. Internal and external environmental factors, such as exposure to diverse microorganisms, ovarian insufficiency, and active vitamin D deficiency, that may contribute to the onset of sarcoidosis must be identified in order to develop strategies for prevention and treatment.